Prognostic significance of aortic valve gradient in patients with severe aortic stenosis undergoing transcatheter aortic valve replacement. Issue 7 (22nd May 2017) - Witberg, Guy; Finkelstein, Arik; Barbash, Issi; Assali, Abid; Shapira, Yaron; Segev, Amit; Halkin, Amir; Fefer, Paul; Ben‐Shoshan, Jeremy; Konigstein, Maayan; Sagie, Alexander; Guetta, Victor; et al.
Abstract: Objective: To evaluate the effect of baseline aortic valve gradient (AVG) both as a continuous and a categorical variable on mortality in patients undergoing transcatheter aortic valve replacement (TAVR), focusing on the high‐gradient severe aortic stenosis (AS) patients. Background: Identifying new predictors of mortality in the TAVR population can help refine risk stratification and improve the patient selection process for this procedure. So far, AVG has mainly been studied as a categorical variable and there is a paucity of data on its prognostic value as a continuous variable, especially in patients with high AVG AS, who constitute the majority of patients referred for TAVR. Methods: We analyzed data on 1, 224 consecutive symptomatic severe AS patients, who underwent TAVR at 3 centers. The relation between pre‐TAVR AVG and mortality was evaluated among all patients and in patients with high AVGs (mean AVG ≥40 mm Hg) using the Cox proportional hazard model adjusting for multiple variables. Results: During a mean follow‐up of 1.8 years, baseline AVG was inversely associated with mortality in the entire cohort and in patients with high AVG AS. By multivariable analysis, patients with mean AVG 40–60 mm Hg and >60 mm Hg had a respective 38% ( P = 0.010) and 61% ( P < 0.001) reduction in mortality compared to patients with mean AVG <40 mm Hg. Every 10 mm Hg increase in mean AVG was associated with 20% reduction in mortality ( P < 0.001). Analyses among patients with high (mean AVG >40 mm Hg) and very high AVG AS (mean AVG >60 mm Hg) yielded similar results (HR = 0.88, P = 0.031, and HR = 0.80, P = 0.019, per 10 mm Hg increase in AVG, respectively). Using peak AVGs and an analysis restricted to patients without reduced ejection fraction yielded consistent results. Conclusions: Baseline AVGs show an inverse association with mortality post‐TAVR. These results were consistent also in patients with high‐gradient AS, suggesting that AVG can be used to identify patients most likely to benefit from TAVR.